2019
DOI: 10.1111/jop.12862
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of nomogram for prediction of malignant transformation in oral leukoplakia: A large‐scale cohort study

Abstract: Purpose Oral leukoplakia (OL) is the well‐known disorder of oral mucosa, which has potential to be malignant and can lead to squamous cell carcinoma (OSCC). In the following study, we developed a comprehensive nomogram for predicting the malignant progression of OL, based on analysis of clinicopathological variables. Methods A retrospective analysis of patients diagnosed with OL was performed between 1998 and 2017 at the Peking University School and Hospital of Stomatology. OL was confirmed by pre‐treatment bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 25 publications
2
42
0
Order By: Relevance
“…Moreover, a study by Rubert et al provides us with information that gender may also influence the risk of malignant transformation of oral leukoplakia. In the study, 57.1% of cases were diagnosed among female patients and 42.9% among male patients, which may lead to a conclusion that female patients might be more prone to malignant transformation of oral leukoplakia [ 29 ], which is the opposite result of the research conducted by Jayasooriya et al [ 28 ], Wang et al [ 27 ], and meta-analysis prepared by Matulić et al, which also revealed that there were no statistically significant differences in malignant transformation of oral leukoplakia between male and female patients [ 30 ]. Nevertheless, returning to the statement that the age of patients may influence the clinical symptoms of leukoplakia, the study by Rupert et al also seems to confirm this [ 29 ].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, a study by Rubert et al provides us with information that gender may also influence the risk of malignant transformation of oral leukoplakia. In the study, 57.1% of cases were diagnosed among female patients and 42.9% among male patients, which may lead to a conclusion that female patients might be more prone to malignant transformation of oral leukoplakia [ 29 ], which is the opposite result of the research conducted by Jayasooriya et al [ 28 ], Wang et al [ 27 ], and meta-analysis prepared by Matulić et al, which also revealed that there were no statistically significant differences in malignant transformation of oral leukoplakia between male and female patients [ 30 ]. Nevertheless, returning to the statement that the age of patients may influence the clinical symptoms of leukoplakia, the study by Rupert et al also seems to confirm this [ 29 ].…”
Section: Discussionmentioning
confidence: 98%
“…Mostly higher incidence of leukoplakia, in men aged 41–60 years, has also appeared in the work of some authors [ 8 , 18 , 25 ], although some investigators have shown that the incidence of leukoplakia in women and men is equal [ 4 ], or even higher in women [ 17 ]. According to Wang et al, in a retrospective study including 875 patients from a Chinese population, women more often had oral leukoplakia (the ratio of men to women for oral leukoplakia was 1:2) and the malignant transformation rate in women (14.4%) was higher than in men (9.4%) [ 27 ]. In our retrospective study, leukoplakia was diagnosed slightly more often in men, but women accounted for 47.1% of all diagnosed patients (220 men and 196 women with leukoplakia lesions).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the proportion (14.5%) was within the rate (12.2%-17.9%) of malignant transformation of oral leukoplakia from China. 24,25 Although it was moderate efficacy that that AUC of DNA aneuploidy was 0.735 (sensitivity, 61.5%; specificity, 77.5%) for discrimination of dysplasia from general OPMD, it was well-recognized efficacy that the AUC of DNA aneuploidy was 0.851 (sensitivity, 84.5%; specificity, 80.2%) for detection of carcinoma in general OPMD. Correspondingly, the optimal criteria of DNA aneuploidy were classified from at least one aneuploid cell with DI ≥ 2.3 to aneuploid cell with DI ≥ 3.5.…”
Section: Discussionmentioning
confidence: 98%
“…Oral leukokeratosis that will subside after the control of local factors such as smoking and local physical stimulation is not included in this category. With a high risk of malignant transformation (estimated overall rate: 3.5%, range from 0.13% to 34.0%), [3][4][5][6] OLK can affect the physical and mental health of patients to various degrees. [7][8][9] According to the clinical manifestations, OLK can be classified into 2 types with significant differences in the rate of malignant transformation: homogeneous vs nonhomogeneous (3.0% vs 14.5%, P < .01).…”
mentioning
confidence: 99%